Dampak Penggunaan Medsos Terhadap Perilaku Sosial Peserta Didik di Kelas Tinggi (International Forum of Researchers and Lecturers, 2025)
This research stems from the fact that some students need support to understand the benefits of appropriate social media use, which affects their social behavior in the school environment. This will impact students' social behavior at a higher level, which should be more enjoyable as social media is more often used for entertainment rather than learning purposes. The benefits of using social media, such as improving student understanding, depend on how effectively each student utilizes it. However, it also has its downsides; for example, if students and teenagers are not properly supervised, they can be easily influenced by the negative side of social media use. This study will show the impact of social media on students' social behavior at a higher level.